György Vókó: 1946-2021 (Academic Journal of Internal Affairs, 2021)
György Vókó, a retired head of department, who died at the age of 75, is Director of the National Institute of Criminology, Hungarian Academy of Sciences doctor, professor of the Faculty of Law and Political Science of the Pázmány Péter Catholic University instructor of emeritus.
Keywords: memoir